2001
DOI: 10.1590/s0041-87812001000100004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the treatment of sepsis with vancomycin in term newborn infants

Abstract: A prospective study was conducted to determine if standardized vancomycin doses could produce adequate serum concentrations in 25 term newborn infants with sepsis. Purpose: The therapeutic response of neonatal sepsis by Staphylococcus sp. treated with vancomycin was evaluated through serum concentrations of vancomycin, serum bactericidal titers (SBT), and minimum inhibitory concentration (MIC).Method: Vancomycin serum concentrations were determined by the fluorescence polarization immunoassay technique , SBT b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Therapeutic trough vancomycin concentrations range from 5 mg/L to 25 mg/L [8,12]. Thus, reports on the number of subjects with sub-therapeutic levels of vancomycin show wildly varying results, with reported percentages ranging from 24% to 58% [13,14]. In the present study, approximately half of the neonates had initial trough serum concentrations in the sub-therapeutic range after the administration of the recommended dosing regimen.…”
Section: Discussionmentioning
confidence: 66%
“…Therapeutic trough vancomycin concentrations range from 5 mg/L to 25 mg/L [8,12]. Thus, reports on the number of subjects with sub-therapeutic levels of vancomycin show wildly varying results, with reported percentages ranging from 24% to 58% [13,14]. In the present study, approximately half of the neonates had initial trough serum concentrations in the sub-therapeutic range after the administration of the recommended dosing regimen.…”
Section: Discussionmentioning
confidence: 66%
“…1,15,19,20) A study on the relationship between peak concentrations of VCM and the therapeutic response in the newborn infants with bacteremia showed that the median peak VCM concentrations were 27.4 mg/ml and 16.4 mg/ml in the patients with good and bad evolution, respectively. 21) However, these differences were not significant. In the present study, the duration of treatment for the TDM Group A, in which the peak VCM concentrations within 10 d of Day 1 were 25 mg/ml or above, was significantly shorter than that of the Group B, in which the peak concentrations were below 25 mg/ml.…”
Section: Discussionmentioning
confidence: 79%
“…[29][30][31] However, results of studies [31][32][33][34] in human patients and experiments with animal models indicate that measurement of blood urea and serum creatinine over a period of 5 days accurately detects changes associated with nephrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%